Haemodynamic response to intravenous vasopressin and nitroglycerin in portal hypertension. Issue 3 (March 1988) - Westaby, D; Gimson, A; Hayes, P C; Williams, R
Abstract : We have evaluated the haemodynamic effects of intravenous (iv) nitroglycerin (NG) and vasopressin (VP) alone and in combination, in 12 patients with cirrhosis and recent variceal haemorrhage (two to seven days). Nitroglycerin infusion alone (200 micrograms/min) produced a significant fall in portal pressure (WHVP-FHVP) (from 16.4 (0.6) to 13.3 (1.2) mmHg; p less than .001) associated with hypotension (mean arterial pressure from 95 (7) to 78 (9) mmHg; p less than 0.005). Vasopressin alone (0.4 IU/min) reduced portal pressure (20.7 (1.3) to 14.0 (1.3) mmHg; p less than 0.001), but there was considerable variation in the systemic haemodynamic changes with increased cardiac output in four of six patients. The combination of vasopressin and nitroglycerin corrected all systemic haemodynamic disturbances produced by either agent alone. This combination led, however, to a further reduction in portal pressure (from 13.7 (0.9) to 11.7 (0.7) mmHg p less than 0.01). These results show that: (1) intravenous nitroglycerin reduces portal pressure, and (2) the combination of nitroglycerin and vasopressin reverses systemic haemodynamic disturbances produced by either agent alone and leads to a further decrease in portal pressure.